2005
DOI: 10.1097/01.pcc.0000160658.35437.65
|View full text |Cite
|
Sign up to set email alerts
|

Histologic chorioamnionitis and severity of illness in very low birth weight newborns

Abstract: Our findings indicate that HCA is a major predictor of morbidity and mortality in VLBW newborns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
43
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 39 publications
3
43
0
Order By: Relevance
“…In 19 of 27 studies, the patient characteristics were clearly differentiated between the CA and non-CA groups. In 15 out of these 19 studies, there was a significantly higher GA at birth among the non-CA group compared to the CA group [21,27,28,36,41,43,45,56,57,58,60,62,63,64,65]. Only 8 studies showed no difference among the groups in terms of GA [42,43,47,50,52,58,61,66].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 19 of 27 studies, the patient characteristics were clearly differentiated between the CA and non-CA groups. In 15 out of these 19 studies, there was a significantly higher GA at birth among the non-CA group compared to the CA group [21,27,28,36,41,43,45,56,57,58,60,62,63,64,65]. Only 8 studies showed no difference among the groups in terms of GA [42,43,47,50,52,58,61,66].…”
Section: Methodsmentioning
confidence: 99%
“…The clinical profile of the infants and the methodological characteristics of the studies have been summarized in online supplementary appendix A (see www.karger.com/doi/10.1159/000357556 for all online suppl. material) [36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69]. …”
Section: Methodsmentioning
confidence: 99%
“…It effects are likely mediated by a fetal inflammatory response syndrome with multiple organ failure and dysfunction (4). CA can be considered a "natural" model for neonatal illness severity in high-risk newborns admitted to the neonatal intensive care unit (NICU) (5)(6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…In particular, a PI value of ^ 1.24 has been shown to be an accurate predictor for assessing the severity of neonatal illness [5] . In addition, early PI monitoring has been shown to be helpful in iden-tifying preterm and term neonates born to mothers with chorioamnionitis, a major predictor of morbidity and mortality in very low birth weight infants [8][9][10] . Moreover, PI values might be a useful additional tool for early detection of duct-dependent systemic circulation (left heart obstructive disease) [11] .…”
Section: Introductionmentioning
confidence: 99%